Classical extension of quantum-correlated separable states - Bellomo, Guido (2015)
Li and Luo [Phys. Rev. A 78 (2008) 024303] discovered a remarkable relation between discord and entanglement. It establishes that all separable states can be obtained via reduction of a classically-correlated state "living" in a space of larger dimension. Starting from this result, we discuss here an optimal classical extension of separable states and explore this notion for low-dimensional systems. We find that the larger the dimension of the classical extension, the larger the discord in the original separable state. Further, we analyze separable states of maximum discord in ℂ2 ⊗ ℂ2 and their associated classical extensions showing that, from the reduction of a classical state in ℂ2 one can obtain a separable state of maximum discord in 2 2.